Principal component analysis of odor coding at the level of third‐order olfactory neurons in Drosophila. (7th October 2013) - Hiroi, Makoto; Ohkura, Masamichi; Nakai, Junichi; Masuda, Naoki; Hashimoto, Koichi; Inoue, Kiichi; Fiala, André; Tabata, Tetsuya
<x xml:space="preserve">Abstract</x> Olfactory information in Drosophila is conveyed by projection neurons from olfactory sensory neurons to Kenyon cells (KCs) in the mushroom body (MB). A subset of KCs responds to a given odor molecule, and the combination of these KCs represents a part of the neuronal olfactory code. KCs are also thought to function as coincidence detectors for memory formation, associating odor information with a coincident punishment or reward stimulus. Associative conditioning has been shown to modify KC output. This plasticity occurs in the vertical lobes of MBs containing α/α' branches of KCs, which is shown by measuring the average Ca2+ levels in the branch of each lobe. We devised a method to quantitatively describe the population activity patterns recorded from axons of >1000 KCs at the α/α' branches using two‐photon Ca2+ imaging. Principal component analysis of the population activity patterns clearly differentiated the responses to distinct odors.